Implementasi Sistem Customer Relationship Management (CRM) Berbasis Website untuk Pengelolaan Membership dan Loyalty Point pada CV. Honda Karya Utama Kisaran - Wisnani Risa Rezkika; Masitah Handayani; Mustika Fitri Larasati (LPPM Universitas Bina Sarana Informatika, 2026)
Increasing competition in the automotive industry requires companies to strengthen long-term relationships with customers. CV. Honda Karya Utama Kisaran currently manages customer and transaction data without an integrated membership or loyalty point system, making it difficult to identify repeat customers and evaluate customer loyalty. This study aims to design and implement a web-based Customer Relationship Management (CRM) system integrated with membership and loyalty point features. The system was developed using the Waterfall model, including requirement analysis, system design with UML, implementation using PHP and MySQL, black-box testing, and system deployment. The results show that the system integrates customer and transaction data into a centralized database and automatically calculates loyalty points based on customer transactions. After implementation, the transaction recording process became more efficient, reducing recording time from approximately five minutes to two minutes per transaction. In addition, the system enables the identification of active customers and repeat transactions, supporting data-driven promotional strategies and improving operational efficiency in managing customer relationship